The politics of early school leaving: how do the European Union and the Spanish educational authorities 'frame' the policy and formulate a 'theory of change'. Issue 1 (2nd January 2018) - Rambla, Xavier
Abstract: The article analyses the interaction between the European Commission and a sample of educational authorities in Spain with regard to the policy against early school leaving. Although this member state scores the highest proportion of early school leavers, apparently it is not adopting some key recommendations issued by the Commission. In fact, while educational policy studies regret this 'resistance', studies on EU policies suggest that the EU and the states normally negotiate the ambition and the evaluation of policies in complex ways. In this vein, the article draws on a method of discourse analysis to observe to what extent these educational authorities 'frame' the policy in the same terms and share a similar rationale or 'theory of change'. In brief, the findings point out that the EU, the Government of Spain and two significant regional governments retrieve a similar 'frame' but do not agree regarding the 'theory of change'.